Pengaruh Penggunaan Metode Al-Barqy Terhadap Kualitas Bacaan Al-Qur’an Siswa Pada Mata Pelajaran Al-Qur’an Di MTs Nurul Hasanah Walbarokah - Elvianti, Chairunnisa; Setiawan, Hasrian Rudi (Yayasan Rahmat Islamiyah, 2024)
This research was conducted with the aim of finding out the effect of using the al-barqy method on the quality of Al-Qur’an reading at MTs Nurul Hasanah Walbarokah. This research uses quantitative experimental. This study looked at 32 seventh-grade kids who were taking Al-Qur’an classes. Data is gathered through tests, observations, and writing things down. In the meantime, statistical data analysis, or SPSS, was used to look at the data in this study. Before the al-Barqy method was used, the results of this study in class VII at MTs Nurul Hasanah Walbarokah were 68.75% low, 25.00% middle, and 0% high. But when the al-Barqy method was used, the low category went up by 3.125%, the medium category by 40.625%, and the high category by 56.25%. This means that after the al-barqy method was used to improve the quality of reading the Al-Qur’an in Al-Qur’an classes at MTs Nurul Hasanah Walbarokah, there were no students who did not meet the Minimum Completeness Criteria (KKM).